Searching for a New Way of Thinking Society for Today-Noospheric Social Quality - Bobkov, Vyacheslav Nikolayevitch; Bobkov, Nikolay Vyacheslavovic; Herrmann, Peter (Economy of Regions, 2016)
Obviously, we face an economic crisis that dominates the headlines of daily newspapers, academic journals and features as the title of TV-and-radio casts alike. And, not withstanding political differences, there is widespread consensus that the economic crisis is only the tip of an iceberg. However, there is little readiness to go beyond the inherited fundamental assumptions of a “modern industrial capitalist market society”. The article argues that all the categories are increasingly under threat. The social quality, the quality of life and the noosphere paradigm of global social development offer space for considerations that question societal developments not only on the phenomenological level. Instead, the authors ventilate gnoseological, ontological and axiological prerequisites of sustainable global social development. The noosphere paradigm is enriched with the theories of social quality and the quality of life, thus contributing to the wider and diverse debates on what can be called people’s humanistic socialism. In view of the complexity of the impending transition from the present to a future global society with people’s humanistic socialism, it is necessary to plan it thoroughly, beginning with the support of the processes and institutions that currently provide a seedbed; developing new transformational forms of the future features of global society has to go hand in hand with this. It makes sense to carry on with the conceptualization of questions bearing on the formation of nooshpheric social quality and its design.